Quality of Sous Vide-Cooked Pork Loin Stored in Refrigerated Conditions - Lidia Kurp; Marika Bielecka; Marzena Danowska-Oziewicz (Applied Sciences)
The sous vide cooking method offers advantage in preparing meat dishes in advance. This study aimed to evaluate the effect of refrigerated storage on the quality attributes of pork loin sous vide cooked under selected, optimised temperature and time parameters. Pork loin was cooked at varying temperatures (57–63 °C) and times (3.5–5.5 h), followed by refrigerated storage for up to 7 days. Analytical methods, including TBARS index for lipid oxidation, instrumental colour measurement, texture analysis, and volatile compound profiling, were used to assess changes in meat quality over time. The results indicated that heat treatment and storage time significantly influenced lipid oxidation, colour, and texture. The highest TBARS values were observed at higher cooking temperatures (61 °C and 63 °C), reflecting increased lipid oxidation. Colour changes were also temperature- and time-dependent, with a decrease in redness (a*) and an increase in lightness (L*) and yellowness (b*). Sensory evaluation revealed that juiciness, aroma intensity, tenderness, and flavour acceptability were strongly correlated with overall acceptability, while physical characteristics like colour and texture had a lesser impact. The study highlights the impact of sous vide cooking parameters on the quality and sensory attributes of pork loin, suggesting that optimised heat treatment can help preserve desirable meat characteristics during refrigerated storage.